Evaluation of leadership styles under the view of members of the 14th federal staff in Patos-PB (Research, Society and Development, 2019)
Considering the context of studies on leadership, the Behavioral Theory stands out, which describes three styles of leader: autocratic, democratic and liberal. Subsequently, organizations also came to recognize the charismatic leader, who influences those led from inspiration. Given the above, this research aimed to evaluate the leadership styles from the point of view of members of the staff of the 14th Federal Court in Patos-PB. The research is classified as exploratory and descriptive, having a qualitative and quantitative approach, whose data collection was based on a questionnaire adapted from Accioly (2006), containing questions about the profile of the interviewees. As for data collection, this is a case study, it was observed that the federal public agency is composed of 30 employees divided into the functions of Magistrate, Director, civil servants, interns, conciliators and outsourced, characterizing themselves as the research population. However, the survey was conducted only with public servants and interns, which obtained a total of 12 respondents, characterized as a sample studied. After analyzing and discursing the results, it was found that, according to the postures pointed out by members of the staff, the autocratic style of leadership is the predominant one. Despite this, the staff considered motivating the presence of managers to the work environment.